What Teachers Perceive in Children from Divorced Parents - Donoso Niemeyer, Tania (Revista de Psicología, 2002)
This pilot study explores the preschool teacher´s perception and knowledge of a sample of 23 middle class preschooler´s experience of their parent´s divorce. It was applied the “Divorce Experiencie Scale” (Donoso & Wilson, 1999, teacher´s seccion). It is explored the teacher´s percepcion of the children´s experience of their parent´s divorce in the following aspects: a) responsability atributions, b) conductual reactions, c) emotional reactions, d) parent´s reconciliation fantasies, and e) behavioral changes at school in the relationship with their teachers, schoolmates and school activities. It´s described how the preschool teachers take notice of the children´s parents divorce; how they cope with the children living this life situation, their proffesional competence feelings, and their capacitation needs of improving their knowledge in the field of divorce.